Pengaruh Persepsi Harga terhadap Minat Beli pada Skincare - Indah Mufidah; Didit Darmawan (Journal of Management and Social Sciences, 2025)
This study adopts a qualitative type through a literature study approach to analyze the effect of price perception on purchase interest in Skincare. Data were collected from relevant literature sources, such as books and journal articles, which discuss the relationship between price perception and purchase interest. Data analysis was carried out using a content analysis approach, where researchers coded data based on relevant themes. The results of the study indicate that price perception has a significant positive effect on consumer purchase interest. The increasing good consumer views on product prices, the greater their chances of deciding to purchase. This study emphasizes the importance of the right pricing strategy to attract buyers' attention. Therefore, companies are advised to increase perceived value through promotions and services, as well as open up continuous exploration space related to other aspects that impact purchase interest.